Episode 37: Infectivity of PRRS virus variants - Schieck Boelke, Sarah; Melini, Marcello (My University, 2023)
In the podcast Swine Extension Educator Sarah Schieck Boelke speaks with PhD student Marcello Melini about his research on the infectivity of PRRS virus variant 1-4-4 as it comparies to other PRRS virus variants.
Runtime 23:48